Near‐infrared light reduces glial activation and modulates neuroinflammation in brains of diet‐induced obese mice. (1st February 2022) - Saieva, Salvatore; Fracassi, Anna; Zhang, Wenru; Marcatti, Michela; Taglialatela, Giulio
Abstract: Background: Obesity and type 2 diabetes (T2D) are major risk factors for Alzheimer's Disease (AD), which are characterized by neuroinflammation, a key event in neurodegeneration. Hippocampal neuroinflammation, in rodents, correlates with poor memory performance, while in humans, growing evidence shows that obesity increases three times the risk of developing AD. The overall objective of our work is to reduce the impact of obesity/T2D‐driven neuroinflammation, which in turn may lead to dementia. Recently, near‐infrared light (NIR) has gained growing interest, showing improvement of learning and memory in both humans and animal models. We previously reported that a transcranial delivery of NIR reduced Aβ and Tau pathology and improved memory function in mouse models of AD. Here, we tested whether NIR light may prevent obesity‐induced neuroinflammation, in a diet‐induced obese (DIO) mouse model. Methods: 5‐weeks old wild‐type mice were fed a high‐fat diet (HFD) for 12 weeks to induce obesity prior the beginning of treatment, which consisted of a transcranial delivery of NIR light for 4 weeks throughout daily sessions of 90 seconds each. After sacrifice, we performed free‐floating immunofluorescence of brain slices stained for microglia and astrocytes markers to evaluate glial activation, and quantitative real‐time PCR to evaluate the expression levels of inflammatory cytokines and neurotrophic factor BDNF. Results: Immunofluorescence showed that, in both hippocampus and cortex, HFD caused increased expression of CD68 (activated microglia) and GFAP (astrocytic marker), which were reversed by NIR light treatment. Also, PCR analyses showed that, only in the hippocampus, HFD caused a significant increase of pro‐inflammatory IL‐1β and TNF‐α, which was reversed by NIR; likewise, the anti‐inflammatory IL‐10 was increased in HFD mice, likely due to a compensatory mechanism, and returned to basal levels after NIR light treatment. Also, the neurotrophic factor BDNF is increased in HFD mice treated with NIR light, compared to HFD not‐treated mice. Conclusions: Our results show a reduction of glial activation and pro‐inflammatory cytokines after NIR light treatment, perhaps driven by a BDNF‐dependent mechanism. This evidence poses NIR light as a potential preventive therapeutic approach against obesity‐induced CNS deficits that are known to concur to AD neuropathology.